1994
DOI: 10.1111/j.1524-4725.1994.tb03220.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Aspects of Venous Ulceration

Abstract: Inflammatory mechanisms play a significant role in the pathogenesis of venous disease but the exact mechanisms producing venous ulceration remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…It is estimated that the Health Service in the United Kingdom spends £600 million per annum 4 on man-agement of this problem, 4 which amounts to nearly 2% of the total health-care expenditure.Among volunteers without venous disease, leukocyte sequestration in the lower limb and white blood cell activation have been produced by means of experimental venous hypertension lasting 30 minutes. 5 At the same time various endothelial factors are released, suggesting that this stimulus is enough to produce minor endothelial injury. Among patients with venous disease, plasma levels of neutrophil elastase and lactoferrin (a secondary granule enzyme) also are elevated, confirming the presence of a chronic inflammatory state.…”
mentioning
confidence: 99%
“…Silver in ionized form applied in Textus bioactive® dressing is constantly released in small concentrations to the wound. It stimulates production of the growth fac-tors, cytokines and metaloproteinases by macrophages, fibroblasts and keratinocytes in the wound and accelerates the process of proliferation (6,14,15,18,19).…”
Section: Discussionmentioning
confidence: 99%